2019
DOI: 10.1021/acs.jpcc.9b06910
|View full text |Cite
|
Sign up to set email alerts
|

Chemisorption of NO2 on V-Based SCR Catalysts: A Fundamental Study toward the Mechanism of “Fast SCR” Reaction

Abstract: The "fast selective catalytic reduction (SCR)" process, with its superior efficiency, is promising for removing NO x from flue gas with low temperature and high gas velocity. Chemisorption of NO 2 is a crucial step in this heterogeneous catalysis process. In this study, density functional theory calculations and experimental methods were implemented to study the chemisorption behaviors of NO 2 on the industrial V-based SCR catalyst. Both the ( 001) and ( 101) surfaces of the TiO 2 support were applied in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…This led to elongation of one of the N–O bonds to 1.42 Å. Such a feature indicates not only sensoric applications of V 3 S 4 , but can also be useful for the catalytic reduction of NO 2 [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…This led to elongation of one of the N–O bonds to 1.42 Å. Such a feature indicates not only sensoric applications of V 3 S 4 , but can also be useful for the catalytic reduction of NO 2 [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the active sites were covered and the catalyst was deactivated. However, surface NH 4 + of NH 4 HSO 4 can rapidly react with the NO/NO 2 /O 2 mixture under Fast SCR conditions, which will promote the decomposition of deposited NH 4 HSO 4 on the catalyst. After SO 2 injection, the activity of the catalytic filter recovered, which was only 2% lower than that before SO 2 injection, exhibiting excellent sulfur resistance.…”
Section: Resultsmentioning
confidence: 99%
“…In earlier studies, our research team has done much research on the reaction of ammonium bisulfate on a vanadia SCR catalyst. The results show that the presence of NO 2 can accelerate the decomposition of NH 4 HSO 4 deposited on the surface of the catalyst. In addition, the equimolar NO/NO 2 reaction was defined as the “Fast SCR”, because the reaction rate of the Fast SCR is more than 10 times faster than that of the standard SCR . Therefore, sulfur resistance of the catalyst is greatly enhanced in the reaction atmosphere of Fast SCR due to the dynamic balance between deposition and decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…It can be confirmed that the mechanism of CMRT-X catalysts is not fast SCR. 54 Moreover, adsorption of NO + O 2 on the surface of three CMRT catalysts resulted in the formation of eight NO active species: bridged nitrate (1250 and 1606 cm –1 ), 17 monodentate nitrates (1286 and 1488, cm –1 ), 17 , 45 M n + -NO 2 species (1315–1350 cm –1 ), 55 − 57 unstable N 2 O 4 species (1521 and 1522 cm –1 ), 58 ionic nitrates (1457 and 1473 cm –1 ), 49 , 59 bidentate nitrates (1506, 1540, 1555, 1558, and 1583 cm –1 ), 14 , 59 , 60 Ru n + -NO molecules (1890 cm –1 ), 49 , 61 63 M n + -H 2 O (1715–1866 cm –1 ), and adsorbed NO species (1158 cm –1 ) ( Figure 5 b–d). 17 These results suggest that the CMRT-350 catalyst adsorbs most types and amount of NO active species, indicating that the reaction between NO and O 2 is most active on the surface of CMRT-350.…”
Section: Resultsmentioning
confidence: 99%